FENOMENA HATSUNE MIKU DI JEPANG SEBAGAI POPULAR CULTURE - NOVANNY, CELVIN MARADIKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Novanny, Celvin Maradika. 2014. Hatsunne Miku Phenomone in Japan as Popular Culture. Study Program Japanese Literature, Faculty Ilmu Budaya, Brawijaya University. Preceptor I :  Fitriana Puspita Dewi; Preceptor II: Murakami SonokoKeywords : Populer Culture, Hatsune Miku, Vocaloid, Otaku.Japanese popular culture such as anime, manga, fashion, and pop music has been widely known throughout the world. Popular culture occurs as works made favored and fun for everyone else. One of the parts of popular culture in Japan is Hatsune Miku.This thesis uses the approach of mass culture, subculture otaku, and popular culture with the concept of Japanese popular culture. This concept was used to investigate the phenomenon of Hatsune Miku can be famous in Japan.The results of this thesis show that the phenomenon Hatsune Miku became popular, because the participation of Japanese society. For example, among the subcultures that plays an important role in the spread of Hatsune Miku. They act as a consumer and producer of the popularity of Miku.Author suggests to examine the phenomenon Hatsune Miku using other approaches, such as cyberculture approach to examine the role of the internet in the process of deployment Hatsune Miku.